Beginning elementary teachers’ feeling to be integrated: Collaboration and self-concept of professional skills - Losego, Philippe; Amendola, Catherine; Cusinay, Michèle (Swiss Journal of Educational Research, 2018)
This article shows that the feeling of being integrated (subjective insertion) of primary education novice teachers quite slightly depends on usual objective criteria (stability, full-time job, match between the job and the degree), but very sorely on their self-concept of professional skills. Among the perceptions they have of their skills, the subjective insertion first of all is linked to the perception to be competent for collective work. Besides, perceived practices fostering the feeling of being integrated are the usual collective ones featuring the nowadays job of teaching: working in groups, school projects, and notably the systematic sharing of didactic material. However, with respect to subjective insertion, this study challenges the relevance of initiatives and other settings specifically dedicated to novice teachers.